Kronologija izdelave digitalnega modela reliefa Slovenije : Chronology of Digital Terrain Model Production of Slovenia - Tomaž Podobnikar (Geodetski Vestnik, 2003)
In the paper, history of the digital terrain and elevation model (DTM and DEM) production is chronologically described. The first ideas to produce the DTM of Slovenia are from the late sixties of the previous century. In 1973 the production of the ‘DMR 100’ started, the project finished in 1984 and was being updated until 1997. In 1975 the first digital terrain model for entire Slovenia was produced: ‘DMR 500’. Until the end of eighties and in the nineties there was no significant progress regarding DTM production. Since 1995 the ‘DMR 25’ has been produced as a lateral product of the digital orthophoto for scale 1:5000. In 2000 InSAR DMV 25 was produced with radar interferometry and in 2001 ‘DMV 20’ from geodetic data of various quality for 1/8 of Slovenia and vicinity.